2023
DOI: 10.1002/advs.202206836
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Regulation of Interlayer Space of NH4V4O10 for Fast and Durable Zn2+ and NH4+ Storage

Abstract: Layered vanadium‐based oxides are the promising cathode materials for aqueous zinc‐ion batteries (AZIBs). Herein, an in situ electrochemical strategy that can effectively regulate the interlayer distance of layered NH4V4O10 quantitatively is proposed and a close relationship between the optimal performances with interlayer space is revealed. Specifically, via increasing the cutoff voltage from 1.4, 1.6 to 1.8 V, the interlayer space of NH4V4O10 can be well‐controlled and enlarged to 10.21, 11.86, and 12.08 Å, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(7 citation statements)
references
References 50 publications
1
6
0
Order By: Relevance
“…26 Wide interlayer distances of 1 are due to the introduction of macromolecular organic amines N -(2-aminoethyl) piperazine. It has been shown that the large interlayer is beneficial for accelerating the transport of ions in the lattice, 32 which will endow 1 with some interesting properties.…”
Section: Resultsmentioning
confidence: 99%
“…26 Wide interlayer distances of 1 are due to the introduction of macromolecular organic amines N -(2-aminoethyl) piperazine. It has been shown that the large interlayer is beneficial for accelerating the transport of ions in the lattice, 32 which will endow 1 with some interesting properties.…”
Section: Resultsmentioning
confidence: 99%
“…These values indicate that the majority of the charges were contributed from the rapid reaction kinetics of a surface-controlled process. 60 The exact contributions from the surface- and diffusion-controlled processes were also calculated. Battery-type materials follow a slow charge-storage process due to the diffusion process while capacitive-type materials follow a fast charge-storage process due to the double-layer/surface charge-transfer process.…”
Section: Resultsmentioning
confidence: 99%
“…After the 10th discharge, the peak of (Zn 3 VO 4 ) 2 appeared and disappeared after charging, further proving that the insertion/extraction of Zn 2+ is reversible after many cycles. The (001) peak intensity of NH 4 V 4 O 10 disappeared after the charging progress, which might be ascribed to the excessive NH 4 + vacancies that cause the deterioration of the crystallinity of NH 4 V 4 O 10 …”
Section: Resultsmentioning
confidence: 99%
“…+ vacancies that cause the deterioration of the crystallinity of NH 4 V 4 O 10 . 45 The ex situ XPS test was utilized to further investigate the mechanism of electrochemical energy storage. Figure 7c shows the XPS spectra for full discharge and full charge.…”
Section: Electrochemical Measurementsmentioning
confidence: 99%